Revenge Fantasies Against Neftegna as a Challenge of Protecting Cultural Heritage: Case Study of Wolayta Sodo Museum, Ethiopia - Birara, Desalegn (Global Journal of Cultural Studies, 2023)
Protection of cultural heritage in Ethiopia has been tough for several reasons. Previous assessments identified salient challenges such as scarcity of resources, shortage of facilities, lack of expertise, deficient budget for the sector, legal holes regarding regulatory role, illicit trafficking & the existence of multiple ports, inadequate awareness about heritages at local communities, poverty, and weather variabilities. This case study had been conducted to examine the impact of social movements on cultural heritages. It emphasizes the demolition of a former satellite palace of H.I.M. Hailesilassie I by local communities with the intention to revenge their grievances of alleged identity suppression. The demolished palace used to serve as a cultural heritage store of Wolayta Zone Museum. Demolition of the palace, besides being historically a valuable house which according to UNESCO was a heritage itself, made heritages that were contained inside, vulnerable to assorted damages. Peoples’ perception of historical facts and themselves has briskly endangered heritages. The study uncovers narratives of emergent identities have catastrophic impact on cultural heritages.